The paths to negative and positive experiences of informal caregiving in severe mental illness: a study of explanatory models - Campos, Luísa (2019)
The experience of caregiving in severe mental illness is a valuable concept for research and clinical practice as it can provide access to the idiosyncratic assessment of negative and positive dimensions of informal caregiving, thus allowing the design of interventions focused on reducing risk factors and promoting protective factors. This study was aimed at testing explanatory models of negative and positive experiences of caregiving considering the role of the caregiver’s perceptions of difficulties, satisfaction, and coping. A convenience sample of 159 informal caregivers of patients with schizophrenia was used in this study. Different variables were considered: (1) perception of difficulties (Caregiver’s Assessment of Difficulties Index); (2) perception of satisfaction (Caregiver’s Assessment of Satisfaction Index); (3) perception of coping (Caregiver’s Assessment of Managing Index); and (4) the experience of caregiving (Experience of Caregiving Inventory). Using structural equation modeling, the results revealed the following: (1) the perception of difficulties and of satisfaction coexist; (2) the negative experiences of caregiving are predominantly explained by the perception of difficulties and of coping with stress; and (3) the positive experiences of caregiving are mainly explained by the perception of sources of intrapersonal satisfaction, while the perception of coping does not have robust predictive value